Нужна ваша !
решите уравнение:
6^{x-2} - (\frac{1}{6} )^{3-x} + 36^{\frac{x-1}{2}} = 246

liza2002623 liza2002623    3   27.09.2019 21:38    1

Ответы
Vkomarova Vkomarova  02.09.2020 07:29

x = 4

Пошаговое объяснение:

6^{x-2} - (\frac{1}{6})^{3-x} + 36^{\frac{x-1}{2}} = 246\\\\6^{x-2} - 6^{x-3} + 6^{x-1} = 246\\\\\frac{6^x}{6^2} - \frac{6^x}{6^3} + \frac{6^x}{6} = 246\\\\\frac{6^x}{36} - \frac{6^x}{216} + \frac{6^x}{6} = 246\\\\6^x = t\\\\\frac{t}{36} - \frac{t}{216} + \frac{t}{6} = 246\\\\6t - t + 36t = 53136\\\\41t = 53136\\\\t = 1296\\\\6^x = 1296\\\\6^x = 6^4\\\\x = 4

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика